Inside CERN's Large Hadron Collider : from the proton to the Higgs boson - Campanelli, M. (Mario) (World Scientific Publishing Co. Pte. Ltd., 2016)
"The book aims to explain the historical development of particle physics, with special emphasis on CERN and collider physics. It describes in detail the LHC accelerator and its detectors, describing the science involved as well as the sociology of big collaborations, culminating with the discovery of the Higgs boson. Readers are led step-by-step to understanding why we do particle physics, as well as the tools and problems involved in the field. It provides an insider's view on the experiments at the Large Hadron Collider."--